2014
DOI: 10.1371/journal.pone.0106809
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in the Developmental Regulation of Aquaporins 1, 3 and 5 during Pregnancy and Lactation in the Rat

Abstract: Milk secretion involves significant flux of water, driven largely by synthesis of lactose within the Golgi apparatus. It has not been determined whether this flux is simply a passive consequence of the osmotic potential between cytosol and Golgi, or whether it involves regulated flow. Aquaporins (AQPs) are membrane water channels that regulate water flux. AQP1, AQP3 and AQP5 have previously been detected in mammary tissue, but evidence of developmental regulation (altered expression according to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…Those authors found that AQP1 expression remained elevated from early to peak lactation, whereas we found that AQP1 expression in the MG decreased during this period. We also found that AQP3 expression remained elevated from day 2 to day 21 of lactation, whereas Nazemi et al [13] found that AQP3 expression decreased from early to peak lactation. Whether these differences reflect between-species or experimental divergence is unknown.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Those authors found that AQP1 expression remained elevated from early to peak lactation, whereas we found that AQP1 expression in the MG decreased during this period. We also found that AQP3 expression remained elevated from day 2 to day 21 of lactation, whereas Nazemi et al [13] found that AQP3 expression decreased from early to peak lactation. Whether these differences reflect between-species or experimental divergence is unknown.…”
Section: Discussionsupporting
confidence: 46%
“…We also find that gene expression for AQP1 and 3, both of which are measures of vascular permeability [52], increases from late gestation to lactation. Nazemi et al [13] also recently reported that expression of AQP1 and 3 in the MG of rats increases between gestation and early lactation. Those authors found that AQP1 expression remained elevated from early to peak lactation, whereas we found that AQP1 expression in the MG decreased during this period.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We also found that, in contrast to AQP-1 and AQP-3, which were predominantly expressed in cytoplasm, the subcellular localization of AQP-5 was exclusively present in nuclei in virgin rats whereas during lactation it was detected in both cytoplasm and nuclei. Nazemi et al also found that the immunohistochemical staining signals of AQP-5 were in mammary epithelial cells and duct system in rats but the signals were mainly in cytoplasm [ 23 ]. Both our study and the report by Nazemi et al show that the staining intensity of AQP-5 was lower than that of AQP-3 in lactating mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, immunohistochemical staining and western blot demonstrated that protein levels of AQP-3 and AQP-5 were significantly increased in lactating rats compared with virgin rats. Nazemi et al investigated the expression of AQP-1, AQP-3, and AQP-5 during pregnancy and lactation in rats and found that, compared with pregnancy stage, the mRNA levels of AQP-1 and AQP-3 were significantly increased at lactation stage [ 23 ]. Similar to the results in this study, they demonstrated significantly higher protein levels of AQP-3 at lactation than at pregnancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%